Multi-contextual perspectives on silence: a narrative case study - Harumi, Seiko (Neofilolog, 2024)
This narrative case study explores ways a Japanese learner of English utilised multiple silences as an interactional resource, enhancing collaborative second language (L2) interaction beyond the classroom while studying abroad in the United Kingdom. The concept of ‘multi-contextual silences’ in this study involves the idea that multi-faceted silences play an integral, harmonious role in creating collaborative interaction in new socio-cultural contexts. Drawing on the concept of global cross-cultural competence, which nurtures all-inclusive views on diverse interactional styles, this study examines a learner’s multi-faceted use of silence enhanced through her unique individual network of practice (INoP) as a social network theory (Zappa-Hollman, Duff, 2015) involving learners’ initiation of agency for social interaction in language socialisation. It should be noted that this study adopts the revised INoP framework, incorporating learner agency enhanced through self-reflection. Its data includes a questionnaire survey and six in-depth interviews on the use of silence and talk during a year-long sojourn. It specifically sheds light on the learner’s facilitative use of silence, manifested in solitude, creative silence in affinity space, sharable co-learning space, and the learner’s use of silence as an active listener in L2 turn-taking practices originating in her emic and culturally oriented interactional perspectives. While challenging perceptions of silence as loneliness or coexistent with interactional struggles, this study illustrates ways in which, from a learner’s perspective, facilitative silence was highly signified and jointly, equally, responsible in talk-in-action. This study suggests the importance of opening up the space L2 learners need to enable them to initiate agency and deepen self and mutual understanding of the multiple roles silence plays in creating interactional opportunities in cross-cultural interaction as seen from diverse viewpoints.